Kajian Literatur Mengenai Efektivitas Kepemimpinan Transformasional Dalam Mendorong Kinerja Karyawan - Nadya Amalya; Rifti Dea Yopi Vita Ayu Irara; Rafika Meilia Sari (Indonesian of Interdisciplinary Journal, 2026)
Transformational leadership plays a crucial role in enhancing employee performance through its four core dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This literature-based study explores how transformational leadership affects employee motivation, engagement, and overall performance by organizing previous research into three primary clusters: the foundational components of leadership, its influence on motivation and organizational commitment, and its impact on employee performance outcomes. The findings reveal that transformational leaders who demonstrate the ability to inspire, empower, and motivate their employees tend to foster higher levels of performance at both individual and team levels. Nevertheless, the effectiveness of this leadership style is not uniform across all settings; it is shaped by contextual variables such as organizational culture and structural conditions. Consequently, further empirical investigations combining quantitative and qualitative methods are essential to validate the proposed conceptual model and deepen the understanding of how transformational leadership operates across different industries, organizational contexts, and cultural environments.